2019
DOI: 10.1101/617464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient use of genomic information for sustainable genetic improvement in small cattle populations

Abstract: 17This paper compares genetic gain, genetic variation, and the efficiency of converting variation into 18 gain under different genomic selection scenarios with truncation or optimum contribution selection 19 in a small dairy population by simulation. Breeding programs have to maximize genetic gain but 20 also ensure sustainability by maintaining genetic variation. Numerous studies showed that genomic 21 selection increases genetic gain. Although genomic selection is a well-established method, small 22 populati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This is in agreement with previous modelling and real data studies. Modelling showed increased genetic gain with genomic selection due to reduced generation interval compared to progeny test, despite reduced selection accuracy [2,3,18]. Real data confirmed that the main driver of genetic gain with genomic selection is the reduced generation interval in sires of sires and sires of dams paths.…”
Section: Genomic Vs Conventional Selectionmentioning
confidence: 75%
See 4 more Smart Citations
“…This is in agreement with previous modelling and real data studies. Modelling showed increased genetic gain with genomic selection due to reduced generation interval compared to progeny test, despite reduced selection accuracy [2,3,18]. Real data confirmed that the main driver of genetic gain with genomic selection is the reduced generation interval in sires of sires and sires of dams paths.…”
Section: Genomic Vs Conventional Selectionmentioning
confidence: 75%
“…The study aimed to evaluate the effect of different investment into phenotyping and genotyping with a simulation of a case-study of a small dairy breeding programme. The simulation mimicked a real dairy cattle population of ~30,000 animals analysed in our previous study [3]. We evaluated 36 genomic scenarios against the conventional scenario, all with equal available resources, but varying extent of phenotyping and genotyping.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations